Materialism and Fashion Consciousness: The Moderating Role of Status Consumption Tendencies and Religiosity - Yeniaras, Volkan (Journal for the scientific study of religion, 2017)
Understanding whether materialistic values translate directly into fashion consciousness or whether it is the status consumption and religiosity that intensifies this relationship within the specifics of explicitly religious consumers is important as fashion consumption appears to occupy a focal position both socially and economically in the lives of many. The Islamic fashion clothing market has begun to attract recent attention and is becoming an area of interest in consumer research. The Turkish Islamic fashion clothing consumptionscape that reached a yearly sales volume of $39 billion in 2013 within a $266 billion global market shows that the explicitly Muslim Turkish consumer gains excitement and pleasure from keeping up-to-date with fashion. Utilizing a unique data set from a survey in Istanbul this article examines the relationships between materialism, status consumption tendencies, intrinsic religiosity, and fashion-novelty consciousness. Strong evidence is found for the positive relationship of materialism to fashion-novelty consciousness. In addition, intrinsic religiosity has been identified to have a negative moderating effect on the materialism-fashion-novelty consciousness association.